Outsmarting social media : profiting in the age of friendship marketing - Bailyn, Evan (Que, 2012)
The war is on . The titanic battle between Google and Facebook has begun- and you can use it to earn more profits! In this book, Evan Bailyn reveals how to attract friendship-based recommendations that will motivate customers more than an y ad or algorithm. Bailyn explains how today's Internet titans are battling to control the future of search and social media, and shows how to use their newest innovations to supercharge your marketing. Packed with case studies from Bailyn's pioneering clients, Outsmarting Social Media offers detailed predictions, careful analysis, and-above all-practical techniques. Read it, get ready for the future, and start reaping the rewards! You'll Learn How To: {u2022} Discover where search and social media are headed, and what it means to you {u2022} Implement strategies that work right now-and will work even better in the future {u2022} Begin profiting from friendships, personal relationships, and tastemakers {u2022} Start using today's new currency of trust: likes, comments, retweets, shares, and video responses {u2022} Use social discovery to deliver messages with stunning personal relevance {u2022} Master the "Search and Sell" method for profitingfrom real-time search {u2022} Sell through personalized recommendations delivered straight to smartphones {u2022} Build your business with Foursquare and Facebook Places check-ins {u2022} Learn effective, low-risk ways to use Groupon-style "daily deals" {u2022} Mine cash from social data in entertainment, beauty, shopping, food, travel, health, and other verticals {u2022} Prepare for emerging shifts in pay-per-click, organic SEO, and web display ad markets {u2022} Preview tomorrow's most exciting new social players, platforms, products, and services.